Dinuclear cobalt complexes with a redox active biphenyl bridging ligand [Co2(BP)(tqa)2](PF6)2 (H4BP = 4, 4′-bis(3-tert-butyl-1, 2-catechol), tqa = tris(2-quinolylmethyl)amine): structure and magnetic properties. Issue 28 (30th June 2021) - Suenaga, Yusaku; Mibu, Takuto; Okubo, Takashi; Maekawa, Masahiko; Kuroda-Sowa, Takayoshi; Sugimoto, Kunihisa
Abstract : [Co2 (BP)(bpqa)2 ](PF6 )2 shows evidence of temperature dependence of the charge distribution, displaying a thermally induced valence tautomeric transition from the lsCo III -[Cat–Cat]-lsCo III to hsCo II -[Sq–Sq]-hsCo II in both solid and solution states. Abstract : The biscatechol, H4 BP (4, 4′-bis(3- tert -butyl-1, 2-catechol)) that can directly connect two redox active catechol moieties was synthesized. Also, tris(2-pyridylmethyl)amine (tpa), bis(2-pyridylmethyl)(2-quinolylmethyl)amine (bpqa), (2-pyridylmethyl)bis(2-quinolyl methyl)amine (pbqa), and tris (2-quinolylmethyl)amine (tqa) were synthesized as terminal ligands of the tetracoordinated tripod. In total, five different dinuclear Co complexes were synthesized from H4 BP with various terminal ligands as follows, [Co2 (BP)(tpa)2 ](PF6 )2 (1 ), [Co2 (BP)(tpa)2 ](PF6 )3 (2 ), [Co2 (BP)(bpqa)2 ](PF6 )2 (3 ), [Co2 (BP)(pbqa)2 ](PF6 )2 (4 ), and [Co2 (BP)(tqa)2 ](PF6 )2 (5 ). After a one-electron oxidation reaction of complex (1 ), complex (2 ), was isolated as a mixed valence state lsCo III -[SQ–Cat]-lsCo III, with an absorption intensity of about 1370 nm (intervalence charge transfer (IVCT) bands) in CH3 CN solution. In addition, an investigation of the magnetic properties of the dinuclear Co complex (3 ) with SQUID showed that the χ M T value gradually increased as the temperature increased from 280 to 380 K. Studies in the solid and solution states using electronic spectra, cyclic voltammetry and SQUID for the above complexes provide clear evidence for three different charge distributions: complexes (1 ) and (3 ) are Co III -[Cat–Cat]-Co III, complex (2 ) is Co III -[Sq–Cat]-Co III, complexes (4 ) and (5 ) are Co II -[Sq–Sq]-Co II . Of the five cobalt dinuclear complexes, only complex (3 ) shows evidence of the temperature dependence of the charge distribution, displaying a thermally induced valence tautomeric transition from the lsCo III -[Cat–Cat]-lsCo III to hsCo II -[Sq–Sq]-hsCo II in both solid and solution states. However, this valence tautomeric step is incomplete at 380 K, with the  χ M T  value of hsCo II -[Sq–Sq]-hsCo II . This suggests that the steric hindrance of the quinolyl rings around the Co ion produces a coordination atmosphere that is weaker than that observed with pyridyl rings, which facilitates a change in the Co III ions to Co II .